Coupling Between Carbon and Nitrogen Metabolic Processes Mediated by Coastal Microbes in Synechococcus-Derived Organic Matter Addition Incubations - Xie, Rui; Wang, Yu; Chen, Qi; Guo, Weidong; Jiao, Nianzhi; Zheng, Qiang (Frontiers in Microbiology, 2020)
Phytoplankton are major contributors to labile organic matter in the upper ocean. Diverse heterotrophic bacteria successively metabolize these labile compounds and drive elemental biogeochemical cycling. We investigated the bioavailability of Synechococcus-derived organic matter (SOM) by estuarine and coastal microbes during 180-day dark incubations. Variations in organic carbon, inorganic nutrients, fluorescent dissolved organic matter (FDOM), and total/active microbial communities were monitored. The entire incubations could be partitioned into three phases (labeled I, II, and III) based on the total organic carbon consumption rates of 6.38-7.01, 0.53-0.64, and 0.10-0.13 μmol C L−1 day−1, respectively. This corresponded with accumulation processes of NH4+, NO2-, and NO3-, respectively. One tryptophan-like (C1) and three humic-like (C2, C3, and C4) FDOM components were identified. The intensity variation of C1 followed bacterial growth activities, showing a labile DOM characteristic. C2, C3, and C4 displayed labile, semi-labile, and refractory DOM characteristics, respectively. Alphaproteobacteria, Gammaproteobacteria, Bacteroidetes, and Actinobacteria dominated the quickly-consumed process of SOM (phase I) coupled with a substantial amount of NH4+ generation. Thaumarchaeota became an abundant population with the highest activities in phase II, especially in the free-living size-fraction, and these organisms could perform chemoautotroph processes through the ammonia oxidation. Microbial populations frequently found in the dark ocean, even the deep sea, became abundant during phase III, in which Nitrospinae/Nitrospirae obtained energy through nitrite oxidation. Our results provide greater insight into the carbon and nitrogen coupling processes mediated by coastal microbial metabolizing phytoplankton-derived organic matter.